Probing the Role Played by Magnetic Fields in Star Formation with BLASTPol - Fissel, Laura Marion
BLASTPol, the Balloon-borne Large Aperture Submm Telescope for Polarimetry, measures linearly polarized Galactic dust emission in order to map magnetic field morphology in nearby molecular clouds. The role played by magnetic fields in providing support against gravitational collapse of clouds and cores and in forming observed cloud morphology is a key outstanding question in our understanding of star formation. BLASTPol has the unique combination of sensitivity to large scale magnetic fields, and sub-arcminute resolution necessary to trace fields into prestellar cores and dense filaments. Thus BLASTPol provides a crucial link between the low resolution Planck all sky maps and the detailed but narrow field-of-view capabilities of ALMA. The telescope operates simultaneously in three bands at 250, 350 and 500 microns which span the SED peak of 10-20K cold dust. This thesis gives an overview of the instrument, with special focus on the telescope motor control and scanning strategy. BLASTPol has had two science flights, both launched from Antarctica. The first flight began in December 2010 and lasted for 9.5 days. The 2010 flight had a number of problems, most significantly a damaged IR blocking filter which degraded the optical performance of the telescope. The second BLASTPol flight began in December 2012 and had much better instrument performance resulting in 12.5 days of science data. The performance of the instrument is reviewed, with the goal of providing insight for future BLASTPol flights and balloon telescopes. Reduction of the 2010 flight data was challenging because of the systematics associated with the damaged IR blocking filter. A review is given of the data reduction pipeline, instrumental polarization characterization, and a series of null consistency tests designed to reject polarization pseudo-vectors contaminated by systematics. This pipeline was tested with simulated timestreams which show that the BLASTPol instrument can be used to reconstruct polarization morphology. The 2012 data is of better quality and preliminary data reduction products have been run through the 2010 analysis pipeline. Though the resulting maps are preliminary they highlight the potential of these data to provide the most detailed maps to date of magnetic field morphology in molecular clouds. PhD